Granulomatous/sarcoid‐like reactions in the setting of programmed cell death‐1 inhibition: a potential mimic of disease recurrence. (1st September 2019) - Hiraki, Tsubasa; Hatanaka, Miho; Arimura, Akiko; Kawahira, Hisao; Kirishima, Mari; Kitazono, Ikumi; Horinouchi, Michiko; Higashi, Michiyo; Kanekura, Takuro; Tanimoto, Akihide
Abstract: Nivolumab and pembrolizumab are humanized IgG4 monoclonal antibodies against programmed cell death 1 (PD‐1). Although these agents are effective in treating advanced melanoma, non‐small‐cell lung carcinoma, and other types of cancers, various adverse events have been reported. Cutaneous adverse events are particularly prevalent and, while granulomatous/sarcoid‐like reactions are uncommon, they are increasingly recognized as immune‐related adverse events associated with immune checkpoint inhibitors. Herein, we report two cases of granulomatous/sarcoid‐like reaction with foreign material, mimicking metastatic malignancy after PD‐1 inhibitor treatment. Clinicians should be aware of the existence of cutaneous lesions and perform biopsy if needed to prevent misdiagnosis and unnecessary adjustments to immunotherapy.